Managing academic air travel emissions: Towards system-wide practice change. (December 2022) - Tseng, Sherry H.Y.; Lee, Craig; Higham, James
Highlights: Identifies factors that influence academic air travel. Proposes a practice-based academic flying framework. Cognitive norms are a core driver of academics' air travel decisions. Material cultures and practices can facilitate academics' air travel reduction. Changing cognitive norms depends on collective action of all stakeholders. Abstract: The high carbon emissions arising from academic air travel has become a priority issue for university sustainability programmes. However, efforts to mitigate academic air travel emissions requires the commitment and attention of a range of actors. It is essential to comprehensively identify and understand the factors affecting academics' established aeromobility as a critical step towards system-wide practice change. This research explores this issue by proposing a practice-based academic flying framework and empirically applying the framework. This research found that cognitive norms are the key to affecting academic air travel decisions. The change of cognitive norms depends on collective action of all stakeholders. The empirical application allows the framework to align with university practices and provide stakeholders with a sufficient understanding of factors affecting academic air travel practices. We conclude with a call for all stakeholders to collaboratively create an environment that supports academics through a period of post-COVID practice transition.